Penile length and circumference dimensions: A large study in young Italian men. (21st March 2021) - Di Mauro, Marina; Tonioni, Camilla; Cocci, Andrea; Kluth, Luis A.; Russo, Giorgio Ivan; Gomez Rivas, Juan; Cacciamani, Giovanni; Cito, Gianmartin; Morelli, Girolamo; Polloni, Gaia; di Maida, Fabrizio; Giunti, Daniel; et al.
Abstract: The aim of the present study was to evaluate the size of the penis in flaccidity and in erection of Italian men. A total of 4, 685 men living in Italy and who have been visited at the Italian urology operating units were involved in the study between January 2019 and January 2020. Each patient was given details on how to measure their penis (erect length and circumference) in flaccidity and in erection, from the lower base to the distal penile tip. Mean (standard deviation [ SD ]) flaccid penis length was 9.47 (2.69), mean ( SD ) flaccid penis circumference was 9.59 (3.08), mean ( SD ) erect penis length was 16.78 (2.55) and mean ( SD ) erect penis circumference was 12.03 (3.82). At the linear regression analysis, height was associated with flaccid penis length ( β  = 0.04; p ‐value = .01), and erect penis length was ( β  = 0.05; p ‐value < .01) and erect penis circumference was ( β  = 0.06; p ‐value < .01). Height is proportional to the length of the penis in flaccidity and in erection, and to the circumference in erection. The increase in BMI leads to a reduction in the length of the erect penis, as well as weight gain reduces the length of the flaccid penis.